TOWARDS A DECENTRALIZED GOVERNANCE SYSTEM IN EGYPT - Tobbala, Salwa (Journal of Public Policy and Administration, 2019)
Purpose: As Egyptians surprised the World with the January 2011 uprising, they were expressing deep frustrations with a closed and centralized political system that was unwilling to open a space for meaningful public dialogue to meet the social and economic challenges facing Egypt. Methodology: This paper aims to study transitional shift to a decentralized governance through a restructured state system to achieve social and economic success. Since the 80s, decentralization and devolution of power from central to local authorities has been one of the priority public administration tools to make the state more responsive and efficient in delivering public services and promoting economic and social development. Findings: The researcher intends to draw on lessons learned from a decentralized governance reform tools to develop a citizen participation culture and present a roadmap for the Egyptian initiative to implement governance decentralization and provide practical solutions for reforms. Unique contribution to theory, practice and policy: This paper will focus on a roadmap for a decentralized governance system in Egypt.